Sullam al-samawāt - Kāzarūnī, Abū Qāsim, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the Persianate world, encyclopaedias have a long history. Arabic works by Persian authors aside (like Ibn Farīghūn's Jāmiʿ al-ʿulūm , 4th/10th century), the earliest encyclopaedia in Persian is Avicenna's (d. 428/1037) philosophical Dānishnāma-yi ʿAlāʾī . Fakhr al-Dīn Rāzī's (d. 606/1210) Jāmiʿ al-'ulūm on the other hand, is an encyclopaedia on everything there was to know at the time. Philosophical encyclopaedias would usually divide into logic, physics and metaphysics, more general encyclopaedias into the pre-Islamic and Islamic sciences, also called the rational ( ʿaqlī ) and traditional ( naqlī ) sciences, even if a strict separation was not always maintained. In addition, there were also specialized encyclopaedias like Ibn Ḥusayn Jurjānī's medical Dhākhira-yi Khwārazmshāhī (early 6th/12th century). The content of encyclopaedias often being dependent on the author's interests and intellectual horizon, no universal format exists. The present work by Abū Qāsim Kāzarūnī (fl. early 11th/17th century) is an example of a very personal encyclopaedia, treating of religion, philosophy, and literature.